Songket brooch: the potential of Malay Songket motif in jewellery generation ideas - Anuar, N. S. M.; Razaki, N. S. H.; Daud, M. Z.; Hassan, N. N. H. (Academica Press Solutions, 2022)
The research was conducted with the purpose of identifying the potential and significance of Malay Songket motif (Tampuk Manggis) in generation ideas from the context of contemporary jewellery designs. With the main objective to assist researchers in identifying, distinguishing as well as appreciating the Malay Songket motif, this study focused on translating those to creative and innovative designs specifically in contemporary brooch. The Double Diamond method was employed as it is the most befitting in achieving the aims of the study. This model has four main phases which are: 1) Search, 2) Define, 3) Develop and 4) Deliver. This research has 2 phases. Phase 1: Songket Brooch production by Internship students at The Bench Studio and fully completed. Phase 2: User feedback which will be carried out in the next stage. The Copyright Songket Brooch is now in the MyIPO app.